ADHS bei erwachsenen Patienten mit Substanzkonsumstörungen = ADHD in adult patients with substance use disorders - Luderer, Mathias; Kiefer, Falk (Der Nervenarzt, 2019)
Background Attention-deficit/hyperactivity disorder (ADHD) is a common comorbidity in adult patients with substance use disorders (SUDs). The diagnostics and treatment of ADHD with SUD are often a challenge, also with respect to the prescription of stimulants. Recently, a group of international experts developed a consensus paper on the diagnosis and treatment of comorbid ADHD and SUD. In addition, the German S3 guidelines on ADHD have been published, which also give advice on the treatment of ADHD in comorbid SUD. The German S3 guidelines on alcohol-related disorders and methamphetamine-related disorders also address ADHD as a comorbidity. Methods Summary of consensus and guideline recommendations, supplemented with the most recent literature. Conclusion In recent years new findings on the comorbidity of ADHD in patients with SUD have emerged. A series of screening and diagnostic instruments have meanwhile been evaluated in this patient group. The consensus paper and various guidelines therefore provide clinicians with specific help in detecting ADHD in patients with SUD and in conducting further diagnostics and treatment of both disorders. For example, the importance of stimulants in the treatment of patients with SUD and ADHD has significantly changed and first studies on psychotherapeutic interventions specific to this comorbidity are now available.